Review paperModern head and neck brachytherapy: from radium towards intensity modulated interventional brachytherapy - Kovács, György (Journal of Contemporary Brachytherapy, 2014)
Intensity modulated brachytherapy (IMBT) is a modern development of classical interventional radiation therapy (brachytherapy), which allows the application of a high radiation dose sparing severe adverse events, thereby further improving the treatment outcome. Classical indications in head and neck (H&N) cancers are the face, the oral cavity, the naso- and oropharynx, the paranasal sinuses including base of skull, incomplete resections on important structures, and palliation. The application type can be curative, adjuvant or perioperative, as a boost to external beam radiation as well as without external beam radiation and with palliative intention. Due to the frequently used perioperative application method (intraoperative implantation of inactive applicators and postoperative performance of radiation), close interdisciplinary cooperation between surgical specialists (ENT-, dento-maxillary-facial-, neuro- and orbital surgeons), as well interventional radiotherapy (brachytherapy) experts are obligatory. Published results encourage the integration of IMBT into H&N therapy, thereby improving the prognosis and quality of life of patients.